Sustainable 4D Printable Biobased Shape Memory Polymers with Linear Tunability and Multistimuli Actuation for Advanced Applications - Maksims Jurinovs; Madara Veseta; Alisa Sabalina; Pedro E. S. Silva; Artis Linarts; Hossein Baniasadi; Jaana Vapaavuori; Sergejs Gaidukovs (Small Science)
Sustainable materials that effectively combine sophisticated functionality with eco‐friendly materials are critical for next‐generation technologies. Herein, a novel, fully bioderived, 4D printable shape memory polymer with linear tunability and remotely controlled actuation capabilities is presented. Using a linearly tunable matrix based on plant‐derived acrylates with biosourced carbon content ranging from 75% to 87%, such as acrylated rapeseed oil, isobornyl acrylate, and isobornyl methacrylate, precise linear control over glass transition temperatures and mechanical properties is achieved. Furthermore, incorporating up to 0.2 wt% carbon nanotubes enhances electrical and thermal conductivity, enabling Joule heating and light‐driven activation of 4D‐printed actuators. These materials demonstrate remarkable shape fixity and recovery ratios above 90%, validated through thermomechanical analysis. Complex geometries, including auxetic and spiral structures, are successfully fabricated using vat photopolymerization 4D printing, highlighting exceptional resolution and defect‐free printing. Dual‐stage actuation and modular recovery capabilities are demonstrated for multifunctional applications. The materials reported here outperform conventional petroleum‐based acrylates, requiring significantly lower activation voltages while maintaining rapid and efficient recovery. Developed biobased systems open pathways for sustainable applications in soft robotics, aerospace, adaptive medical devices, and smart textiles, paving the way for greener technologies.